Casarett & Doull's Toxicology. The basic science of poisons - Curtis D. (ed) Klaassen
General principles of toxicology. Disposition of toxicants. Non-organ-directed toxicity. Target organ toxicity. Toxic agents. Environmental toxicology. Applications of toxicology.